2014
DOI: 10.5194/acp-14-12415-2014
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and mineralogy of clay minerals in Asian and Saharan dusts and the implications for iron supply to the oceans

Abstract: Mineral dust supplied to remote ocean regions stimulates phytoplankton growth through delivery of micronutrients, notably iron (Fe). Although attention is usually paid to Fe (hydr)oxides as major sources of available Fe, Fe-bearing clay minerals are typically the dominant phase in mineral dust. The mineralogy and chemistry of clay minerals in dust particles, however, are largely unknown. We conducted microscopic identification and chemical analysis of the clay minerals in Asian and Saharan dust particles. Cros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 67 publications
(84 reference statements)
3
68
1
Order By: Relevance
“…The maximum and mean of the mineral data are tabulated (Table 3) (Table 3), with typically higher contributions at higher dust loadings ( Figure 7). The calcite content was up to 90.7%, with a mean of 28.4%, and compared with a mean of 8.2% by Glaccum and Prospero (1980) and lower values by Avila et al (1997) and Jeong and Achterberg (2014). The uncertainty regarding the gypsum contribution in our samples may well have contributed to the observed differences between our data and literature values.…”
Section: Mineralogycontrasting
confidence: 56%
See 1 more Smart Citation
“…The maximum and mean of the mineral data are tabulated (Table 3) (Table 3), with typically higher contributions at higher dust loadings ( Figure 7). The calcite content was up to 90.7%, with a mean of 28.4%, and compared with a mean of 8.2% by Glaccum and Prospero (1980) and lower values by Avila et al (1997) and Jeong and Achterberg (2014). The uncertainty regarding the gypsum contribution in our samples may well have contributed to the observed differences between our data and literature values.…”
Section: Mineralogycontrasting
confidence: 56%
“…Leaching experiments have demonstrated that aerosol Fe solubility is highly dependent on the chemical form and reactivity of Fe in each sample and, in particular that Fe is significantly more labile in clay minerals than in more refractory phases such as quartz which has a low Fe content of typically only a few µg g -1 (Götze et al, 2004) compared to 3-4 % for illite clays (Jeong and Achterberg, 2014;Journet et al, 2008;Schroth et al, 2009). The octahedral sites of clays in the crystal structures of clay minerals can accommodate a significant quantity of Fe.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Overall, the average Fe content for all clay minerals analyzed here is 3.84 wt%. If one considers that there is also chlorite, which has a typical Fe content of 14.8 wt % in desert dust (Jeong and Achterberg, 2014), then the average Fe content in our studied clays rises to 5.7 wt %. This later value is in very good agreement with the average 5.4 wt% Fe content of clay minerals in Saharan dust analyzed by Jeong and Achterberg (2014).…”
Section: Tem-aem Analysesmentioning
confidence: 86%
“…If one considers that there is also chlorite, which has a typical Fe content of 14.8 wt % in desert dust (Jeong and Achterberg, 2014), then the average Fe content in our studied clays rises to 5.7 wt %. This later value is in very good agreement with the average 5.4 wt% Fe content of clay minerals in Saharan dust analyzed by Jeong and Achterberg (2014). 10 Further detailed textural and compositional insights were obtained using the HAADF and EDX detectors of the 15 Titan TEM operated in STEM mode.…”
Section: Tem-aem Analysesmentioning
confidence: 86%
See 1 more Smart Citation